Reflections and Ruminations. Issue 138 (6th June 2013) - Greene, Jennifer C.
Abstract: This is a timely issue on the contributions of mixed methodology to the contemporary demand for credible evaluative evidence on which to base policy and resource‐allocation decisions. The character of evidence—especially evidence on the quality and effectiveness of efforts to improve the life quality or even life chances of many in our societies—requires the best minds from all corners of the evaluation community. The mixed methods voice is needed in the evidence‐based conversation. © Wiley Periodicals, Inc., and the American Evaluation Association .